Cost-effectiveness of alectinib compared to crizotinib for the treatment of first-line ALK+ advanced non-small-cell lung cancer in France. - Marine Sivignon; Rémi Monnier; Bertrand Tehard; Stéphane Roze (PLoS ONE)
The aim of the study is to evaluate the cost-effectiveness of alectinib for first-line treatment of ALK+ advanced non-small-cell lung cancer compared to crizotinib in the French setting. This study used a partitioned survival model, with three discrete health states (progression-free survival, post-progression survival and death). Survival probabilities were derived from a randomised Phase III clinical trial comparing alectinib to crizotinib (ALEX). Beyond the length of the trial (18 months), the efficacy of both treatments was considered equivalent. Occurrence of adverse events or brain metastases were considered as inter-current events. Utilities (and disutilities for intercurrent adverse events) derived from the EQ-5D were applied. Costs were attributed using standard French national public health tariffs. Projected mean overall survival was 4.62 years for alectinib and 4.18 years for crizotinib. Projected mean progression-free survival was 30.30 months for alectinib and 16.13 months for crizotinib. The total number of quality-adjusted life years projected was 3.40 for alectinib and 2.84 for crizotinib. The projected total cost of treatment over the lifetime of the model was € 246,022 for alectinib and € 195,486 for crizotinib. This extra cost was principally attributable to treatment acquisition costs and management before progression. Alectinib was associated with lower costs related to brain metastases and to management post-progression. The incremental cost per life year gained was 115,334 €/year and the incremental cost-effectiveness ratio was 90,232 €/QALY. First-line treatment of ALK+ NSCLC with alectinib provides superior clinical outcomes to crizotinib and is cost-effective in the French context.